Tolerance and cooperation in the religious life of a Roman-catholic community - Uhrin, Michal (Svetovi (Ljubljana), 2024)
This paper aims to reveal specific aspects of religious life in a Roman-Catholic community situated in the Brno-Country district. For this purpose, the fieldwork was conducted in one parish for a period of one year from 30 November 2022. The data collection was mainly based on participant observation and semistructured interviews with ten individuals (three women and seven men; mean age: 36.7 years). Both nativeborn inhabitants and newcomers of diverse professions were intentionally included in the research sample. The content analysis of semistructured interviews was performed in Atlas.ti. It was discovered that tolerance and cooperation are among the most important topics discussed by the informants and play a crucial role in their religious life.
Keywords: Brno; cooperation; Czech Republic; Češka; local communities; lokalne skupnosti; religija; religion; social cohesion; socialna kohezija; sodelovanje; strpnost; tolerance